2022
DOI: 10.1093/ajcn/nqac152
|View full text |Cite
|
Sign up to set email alerts
|

Unprocessed red meat in the dietary treatment of obesity: a randomized controlled trial of beef supplementation during weight maintenance after successful weight loss

Abstract: Background Consumption of unprocessed red meat in randomized trials has no adverse effects on cardiovascular risk factors and body weight, but its physiological effects during weight loss maintenance are not known. Objectives We sought to investigate the effects of healthy diets that include small or large amounts of red meat on the maintenance of lost weight after successful weight loss, and secondarily on body composition (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…However, some observational studies have associated red meat consumption with higher risk of T2D, leading to recommendations to limit its consumption [22,23]. Recommendations to limit red meat consumption are based mostly on observational data, whereas findings from randomized clinical trials usually have found a neutral effect of red meat consumption on health outcomes [24][25][26][27][28]. A recent meta-analysis found no differences in most glycemic and insulinemic risk factors associated with T2D when comparing reduced or no red meat diets with diets that contained red meat [29].…”
Section: Introductionmentioning
confidence: 99%
“…However, some observational studies have associated red meat consumption with higher risk of T2D, leading to recommendations to limit its consumption [22,23]. Recommendations to limit red meat consumption are based mostly on observational data, whereas findings from randomized clinical trials usually have found a neutral effect of red meat consumption on health outcomes [24][25][26][27][28]. A recent meta-analysis found no differences in most glycemic and insulinemic risk factors associated with T2D when comparing reduced or no red meat diets with diets that contained red meat [29].…”
Section: Introductionmentioning
confidence: 99%